Consumer Responsiveness towards SMS Advertisements and Its Effectiveness in the Present Scenario - Hundal, B.S.; Grover , Saurabh (Gyan Management Journal, 2011)
SMS marketing is being used by eve,y type of business organization regardless of the size and popularity of business. Bulk SMS services have become one of the most modern and proven marketing tools for enhancing the brand name. An attempt has been made to study the perception of consumers towards SMS Advertisements and effectiveness of the SMS advertisement programmes from the view point of organized retail sector. Factor analysis and cluster analysis has been used to interpret the problem in a more comprehensive way. It has been found that these advertisements are really effective in increasing the sales of the firm and people have positive outlook towards the same.
Keywords: BulkSMS services; Informative and Promotional SMS; DND service